Isotope-Dilution Gas Chromatography–Mass Spectrometry Method for the Analysis of Hydroxyurea. Issue 3 (June 2015) - Garg, Uttam; Scott, David; Frazee, Clint; Kearns, Gregory; Neville, Kathleen
Abstract : Background: Hydroxyurea is used in the treatment of various malignancies and sickle cell disease. There are limited studies on the pharmacokinetics of hydroxyurea, particularly in pediatric patients. An accurate, precise, and sensitive method is needed to support such studies and to monitor therapeutic adherence. We describe a novel gas chromatography–mass spectrometry (GC–MS) method for the determination of hydroxyurea concentration in plasma using stable labeled hydroxyurea 13 C 15 N2 as an internal standard. Methods: The method involved an organic extraction followed by the preparation of trimethylsilyl (TMS) derivatives of hydroxyurea for GC–MS selected ion-monitoring analysis. The following mass-to-charge ( m / z ) ratio ions for silated hydroxyurea and hydroxyurea 13 C 15 N2 were monitored: hydroxyurea—quantitative ion 277, qualifier ions 292 and 249; hydroxyurea 13 C 15 N2 —quantitative ion 280, qualifier ion 295. This method was evaluated for reportable range, accuracy, within-run and between-run imprecisions, and limits of quantification. Results: The reportable range for the method was 0.1–100 mcg/mL. All results were accurate within an allowable error of 15%. Within-run and between-run imprecisions were <15%. Samples were stable for at least 4 hours at room temperature, 2 months at −20°C, and 6 months at −70°C, and after 3 freeze/thaw cycles. Extraction efficiency for 1-, 5-, 10-, and 50-mcg/mL samples averaged 2.2%, 1.8%, 1.6%, and 1.4%, respectively. Conclusions: The isotope-dilution GC–MS method for analysis of hydroxyurea described here is accurate, sensitive, precise, and robust. Its characteristics make the method suitable for supporting pharmacokinetic studies and/or clinical therapeutic monitoring.